Board Process, Capital Structure Decisions and Company Performance - Md Kassim, Aza Azlina; Ishak, Zuaini; Abdul Manaf, Nor Aziah (Canadian Research & Development Center of Sciences and Cultures, 2012)
Previous studies have focused on board structure and company performance. Several numbers of studies have reported less evidence or no consensus on the relationship between the two. Therefore, attention has shifted to board process in order to provide better insight on the quality of the board. With regards to capital structure, the decision is an integral part of strategies implementation and related to company performance. The paper aims to examine three conceptual models on company performance; board process, capital structure decisions and mediation. The study finds insufficient consensus on the association between board process and capital structure decisions. This study incorporate four essential board process attributes namely, performance of independent directors, board’s risks oversight, Chief Executive Officer (CEO)’s performance evaluation and accessibility of information. In addition, the conceptual models on the relationship between board process, capital structure and company performance provide an alternative approach unlike the traditional models in corporate governance and finance literatures.